K.Note : Okin Collective - Minja Gu - Nayoungim & Gregory Maass - Choi Jeong Hwa - Kyungwoo Chun - Changwon Lee. - Shin, Nathalie Boseul (S.l. : Total Museum of Contemporary Art, 2014)
Okin Collective ; Gu, Minja ; Nayoungim & Gregory Maass ; Choi, Jeong Hwa ; Chun, Kyungwoo ; Lee, Changwon
boek